The ethics of John: Retrospect and prospects - Watt, Jan Gabriël van der; Dulk, Matthijs den (Biblical interpretation series, 2025)
"Over the past two decades the scholarly conversation has shifted from the practically consensus view that John has little to offer in terms of ethical content to a more robust understanding of how Johannine literature engages ethical questions. This process recently reached a milestone with the publication of two seminal tomes on Johannine ethics by Jan van der Watt. Based on the Radboud Prestige Lectures he delivered on this topic, the present volume evaluates van der Watt's approach by submitting it to critical evaluation by leading specialists in the field, and explores future prospects for the study of Johannine ethics"--
"This volume is based on the Radboud Prestige Lectures delivered by Jan van der Watt in Nijmegen in 2018." (Vorwort)
Keywords: Konferenzschrift -- 2018 -- Nimwegen; Aufsatzsammlung; Ethik; Bibel / Johannesevangelium